Emerging technologies in the Peruvian tourism sector: a bibliometric analysis and perspectives on digital innovation - Luis Antonio Ramirez-Flores (Revista Científica de Sistemas e Informática)
Tourism, as one of Peru's most dynamic economic sectors, faces the challenge of adapting to technological transformations that are redefining the way we travel, manage destinations, and generate value. In this context, emerging technologies such as artificial intelligence, augmented reality, big data, and the Internet of Things are positioned as tools to drive digital innovation in the sector. The objective of this study was to analyze scientific production on emerging technologies applied to Peruvian tourism using a bibliometric approach. The methodology was based on the analysis of 68 scientific articles extracted from the Scopus database, using a search string in English and filtering by affiliation with Peruvian institutions. Bibliometric indicators such as annual production, most productive sources, leading institutions, keywords, collaborative networks, and thematic analysis were applied. The results showed sustained growth in research, with a greater presence of regional universities and a strong connection with technological areas. The conclusion is that there is an expanding academic ecosystem, with practical implications for public policymaking, digital capacity building, and the design of smart tourism destinations in Peru.